The effect of non-genetic factors on milk yield and composition of Red Dane cattle in Zimbabwe - Nyamushamba, G. B.; Chikwanda, D.; Matondi, G H M; Marandure, T; Mamutse, J.; Tavirimirwa, B.; Banana, N Y D; Dhliwayo, M. (Livestock Research for Rural Development, 2021)
A study was carried out to establish non genetic factors affecting milk, butterfat and protein yields in Zimbabwean Red Dane cattle. A total of 1325 unedited 305-day lactation records were obtained from Zimbabwe Livestock Identification Trust herd, with cows calving in the period 2002–2006. The Henderson Type III sum of squares in Genstat edition 14 program was used.